Anisotropy magnetoresistance differential probe for characterization of sub-millimeter surface defects on galvanized steel plate - Nurul A’in, Nadzri; Mohd Mawardi, Saari; Mohd Aufa Hadi, Putera Zaini; Aiman, Mohd Halil; M., Ishak; Tsukada, Keiji (Sage, 2021)
Defects such as cracks can cause dangerous damage to the metal structure and may lead to structural collapses. Cracks can exist in various shapes and sizes where they can start to develop from small scale lower than 1 mm and spread to contribute to the complete fracture of components. Hence, early discovery and monitoring of any cracks in their early stage are crucial to prevent any sudden fatal accidents in the future. This work presents the study and detailed analysis of an ECT probe’s development based on AMR sensors to identify sub-millimeter surface cracks in galvanized steel plates. The probe consists of an excitation coil that induces an eddy current in sample plates and two AMR sensors that detect the differential eddy current-induced magnetic response. A phase-sensitive detection technique with a lock-in amplifier is used to evaluate the magnetic field distribution detected by the AMR sensors. The measured magnetic responses are classified to the depth, width, length, and complex shapes of artificial slits, and the probe is used to perform line scans and 2-D map scans above the slits’ positions. The probe was able to characterize slits with a depth and width as low as 210 and 50 µm, respectively, by using an excitation current of 4 mA at 1 kHz. The slit orientations that were perpendicular to the differential direction of the AMR sensors were clearly visualized, with their estimated lengths showed a good correlation with the physical slit lengths. In the future, the developed system can be expected to help towards the development of a more sophisticated crack detection system where real-time inspections can be realized and applied in various fields.